Enhancing aquaculture sustainability: the role of rice floating beds in improving Gibel carp growth and microbiota composition - Jiang, Yangyang; Sun, Yongxu; Zhou, Beibei; Rong, Chaozhen; Ruan, Shouyun; Wu, Minglin (Frontiers in Marine Science, 2025)
To explore the effects of rice floating beds on fish growth and intestinal microbiota, the present study compared the fish growth performance and the microbial diversity, microbial construction, and microbial composition of water and Gibel carp (Carassius auratus gibelio) intestine in rice floating beds ponds and normal ponds. The results revealed that the Gibel carp raised in rice floating beds ponds exhibited significantly greater body length, body weight, and weight gain rates than those in normal ponds. Microbial community analysis showed enhanced richness and diversity in water and intestine of the rice floating beds group. Furthermore, the assembly processes of these microbial communities were predominantly influenced by stochastic mechanisms in rice floating beds ponds. The bacterial phyla associated with nutrient cycling, such as Cyanobacteria, Chloroflexi, and Ignavibacteria, were significantly assembled in the rice floating beds group. Overall, these results highlight the potential of rice floating bed systems as a sustainable aquaculture technique, fostering improved growth performance and microbial diversity, which are critical for the health of cultured fish.